Developing tomorrow's leaders : context, challenges, and capabilities - Eddy, Pamela Lynn (Futures series on community colleges., 2015)
The contributions of community colleges to society are well-documented. Yet, today's community colleges are at a cross road. Decreases in funding support, a push for college completion, attention on developmental course work, and a host of other demands create a dynamic context for community college operations. Who leads these colleges matters as they face these demands and how they lead influences outcomes. Pending leadership retirements provide a prime opportunity for thi